Representation of Racism Issue in Emergency Movie - Maharani, Claudea Pramesdila; Aisyah, Vinisa Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research analyzes the representation of racism in the film "Emergency," highlighting the racial discrimination faced by the main characters, Sean and Kunle. Roland Barthes' semiotic theory is used to identify and interpret signs in the context of racism. This research uses a qualitative approach and constructivist paradigm approach to examine the reality of racism depicted in the movie scenes. Data was collected through documentation of scenes related to racism. Data analysis was conducted using semiotic methods, dissecting connotations, denotations, and myths as well as Stuart Hall's concept of representation. Purposive sampling was used to select scenes that best represented racism the researcher using observation in digital stream application. Data validity was ensured through triangulation techniques. The research findings revealed two forms of racism depicted in the film, namely individual racism and institutional racism. This research explores the myths and stereotypes associated with the black race in society, including being considered inferior, stupid and criminal. It also examines how institutions contribute to perpetuating racism, with schools inadvertently contributing to racial discrimination and police, despite their legal authority, often reinforcing white supremacy.